Thermal stress during late gestation impairs postnatal growth and provides background for genotype-environment interaction in Hereford-Braford and Angus-Brangus cattle - Alves, Mariana Stucki; Bignardi, Annaiza Braga; Zuim, Deise Mescua; Silva, Joel Alves da; Cardoso, Matheus Gomes Rodrigues; Piccoli, Mario Luiz; Roso, Vanerlei Mozaquatro; Carvalheiro, Roberto [UNESP]; Faro, Lenira El; Pereira, Rodrigo Junqueira; Santana, Mário Luiz (Elsevier, 2022)
Heat stress suffered by pregnant cows can impair fetal development and have negative consequences for the future performance of calves. Thus, our objective was to determine the effect of heat stress during late gestation on birth weight (BW) and postnatal growth traits of Hereford-Braford and Angus-Brangus cattle from Brazil. In addition, we employ a reaction norm model to investigate the genotype by environment interaction (G × E) due to thermal stress in late gestation. The average temperature and humidity index of the last 60 days of gestation (THIg) was chosen as an environmental descriptor. The BW of animals was considerably lower for extreme low and high values of THIg. In contrast, the average daily gain from birth to weaning (ADG) and muscling score at weaning (MUS) were gradually reduced by increasing THIg values by -0.0014 kg /day/THIg -0.0119 units/THIg, respectively. The variation observed for the estimates of variances, direct and maternal heritability for BW, ADG, and MUS suggest that there is substantial heterogeneity of genetic variances along the environmental gradient. Thus, differences in response to selection are expected depending on the level of thermal stress where selection candidates are evaluated. Genetic correlation estimates for direct and maternal effects between distant THIg values differed from unity or were negative for all traits. This was another strong indication that few of the same genes are responsible for the same trait in contrasting thermal environments during late pregnancy. In this sense, the thermal environment during late gestation provides background for G × E and should be appropriately considered in genetic evaluations of Hereford-Braford and Angus-Brangus cattle reared on pasture in (sub)tropical regions.
Keywords: Beef cattle; Cold stress; Fetus; Genetic parameters; Heat stress